In Vitro Antiproliferative Effect of Arthrocnemum indicum Extracts on Caco-2 Cancer Cells through Cell Cycle Control and Related Phenol LC-TOF-MS Identification. (30th September 2013) - Boulaaba, Mondher; Mkadmini, Khaoula; Tsolmon, Soninkhishig; Han, Junkyu; Smaoui, Abderrazak; Kawada, Kiyokazu; Ksouri, Riadh; Isoda, Hiroko; Abdelly, Chedly
Abstract : This study aimed to determinate phenolic contents and antioxidant activities of the halophyte Arthrocnemum indicum shoot extracts. Moreover, the anticancer effect of this plant on human colon cancer cells and the likely underlying mechanisms were also investigated, and the major phenols were identified by LC-ESI-TOF-MS. Results showed that shoot extracts had an antiproliferative effect of about 55% as compared to the control and were characterised by substantial total polyphenol content (19 mg GAE/g DW) and high antioxidant activity (I C 50 = 40 μ g/mL for DPPH test). DAPI staining revealed that these extracts decrease DNA synthesis and reduce the proliferation of Caco-2 cells which were stopped at the G2 /M phase. The changes in the cell-cycle-associated proteins (cyclin B1, p38, Erk1/2, Chk1, and Chk2) correlate with the changes in cell cycle distribution. Eight phenolic compounds were also identified. In conclusion, A. indicum showed interesting antioxidant capacities associated with a significant antiproliferative effect explained by a cell cycle blocking at the G2 /M phase. Taken together, these data suggest that A. indicum could be a promising candidate species as a source of anticancer molecules.